(untitled) (Filološke pripombe, 2019)
The article «Contemporary Slovenian literature and the challenges of globalisation» starts by tracing the structural shifts in contemporary Slovenian literature after 1975, focusing on the crisis of modernism and neoavantgarde, and then the begin- nings of postmodernism and the specific genres of the Slovenian post-modern literature. Also, there were two consecutive phases of Slovenian post-modern prose; what began as political post-modernism later acquired a more metaphysical and autoreferential emphasis. In the recent years new themes and subjects are being intro- duced into contemporary Slovenian prose and plays, justifying the thesis that the most recent Slovenian literature (M. Zupančič, A. Blatnik, D. Jančar) has become socially engaged: mainly in terms of critically reflecting on the globalised world of global consumption, neo-liberal ideologies and the reign of multinational corporations.